1983
DOI: 10.1038/bjc.1983.111
|View full text |Cite
|
Sign up to set email alerts
|

Improving the detection of hepatic metastases by the use of dynamic flow scintigraphy

Abstract: Leeds LS9 7TFIt has been shown that ultrasound and static isotope imaging are relatively insensitive for the detection of lesions <2cm diameter (Bryan et al., 1977). CAT scanning, although apparently more sensitive than these 2 methods still appears to have a limitation in detecting small lesions in the liver (Scherer et al., 1978). However, since it has been established that intrahepatic primary or secondary tumours are associated with an increased hepatic arterial blood flow (Breedis & Young, 1953) and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…The two major fields of those studies include dynamic scintigraphic examinations and more recently color Doppler US. The former is systematically described in the works of Leveson et al [78,79] ; the latter is extensively presented in the studies published by Leen et al [80] . Although the concept of hemodynamic changes due to the presence of hepatic metastases was confirmed experimentally, reproducibility of these techniques was not universally proven [81,82] .…”
Section: Detecting the Occult Colorectal Liver Metastasesmentioning
confidence: 99%
“…The two major fields of those studies include dynamic scintigraphic examinations and more recently color Doppler US. The former is systematically described in the works of Leveson et al [78,79] ; the latter is extensively presented in the studies published by Leen et al [80] . Although the concept of hemodynamic changes due to the presence of hepatic metastases was confirmed experimentally, reproducibility of these techniques was not universally proven [81,82] .…”
Section: Detecting the Occult Colorectal Liver Metastasesmentioning
confidence: 99%
“…t is known from experimental animal studies [1][2][3] and clinical patient studies [4][5][6][7][8][9] that the presence of even microscopic liver metastases is associated with changes in hepatic hemodynamics. The mechanism is not clear, although changes have been shown to originate from the early nonvascular phase of the metastases 3 and may be mediated by circulating vasoactive agents as a response to neoplastic growth.…”
mentioning
confidence: 99%
“…9 Hepatic metastases receive an increased proportion of their blood supply from the hepatic artery than from the portal vein. Changes have been observed on dynamic scintigraphy 1,7,8,10 and Doppler sonography. 4,5,11 The Doppler perfusion index (DPI), defined as the ratio of the hepatic arterial volume flow to the sum of the hepatic artery and portal vein volume flow, has been used to detect the presence of small and occult liver metastases in patients with colorectal cancer.…”
mentioning
confidence: 99%
“…These findings indicate that the presence of overt hepatic tumour results in gross derangements of hepatic blood flow. These changes must be taken into consideration when attempting to potentiate the delivery of cytotoxic drugs to hepatic tumour by manipulation of hepatic haemodynamics.The hepatic perfusion index (HPI), that is the ratio of hepatic arterial to total hepatic blood flow determined by dynamic scintigraphy is elevated in the presence of overt tumour in man (Leveson et al, 1983). Previous studies have suggested that the blood supply to overt liver tumour is derived principally from the hepatic artery (Taylor et al, 1979 Radionuclide studies Ten rats injected intraportally with either viable Walker cells or the same number of dead Walker cells and ten rats receiving saline were anaesthetised with intraperitoneal sodium pentobarbitone and the right common carotid artery exposed through a midline cervical incision.…”
mentioning
confidence: 99%
“…The hepatic perfusion index (HPI), that is the ratio of hepatic arterial to total hepatic blood flow determined by dynamic scintigraphy is elevated in the presence of overt tumour in man (Leveson et al, 1983). Previous studies have suggested that the blood supply to overt liver tumour is derived principally from the hepatic artery (Taylor et al, 1979).…”
mentioning
confidence: 99%